#TITLE_ALTERNATIVE# - KHARISMA SUCIATI (NIM : 13614064), FRIDEYAS
The test results of the removed aircraft components are classified into No Fault Found (NFF), Real Reason Conform (RRC) and Other Defect Found (ODF). Corrective actions will be taken on findings that are classified as RRC and ODF, while the NFF category does not taken any action. In The MRO XYZ Company, for NFF category, the age of component when removed is inserted into the failure data. Moreover, reliability calculation at The MRO XYZ Company uses a 2-parameters Weibull distribution. This will cause unrepresentative reliability calculation. Therefore, it is necessary to evaluate the method. This research calculates the reliability by using the 2-parameters Weibull distribution for the data where the NFF category is included in the failure data and where the NFF category is not included in the failure data. This research then calculates the reliability for the same data using 3-parameters Weibull distribution then compare the results with the reliability calculation above. Location parameter γ calculation use Muralidhar method. This research also developes an Excel VBA macro-based tool for reliability calculation. The failure rates calculated by using the 2-parameters Weibull distribution for several part number data where NFF category is not included into the failure data show a significant different result as compared to the method used by the MRO XYZ, where the difference is affected by the percentage of NFF items in the failure data. The reliability calculation with the 3-parameter Weibull distribution results in a significantly difference failure rates with the reliability calculation results of the 2-parameter Weibull distribution used by the MRO XYZ.